Molecular electronics and electrochemistry: the case of ferrocene-tagged Interfaces and of organic molecular junctions studied by time-dependent methods - Sánchez, Yuliana Pérez [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The understanding of electron transmittance, including electron transfer (ET) and transport, is essential not only for comprehending biological systems but also for developing electrical components in the pursuit of fabricating electronic devices. The quantum rate theory proposes a first-principle fundamental quantum rate ν = e2/hCq, where e is the elementary charge, h is the Planck constant and Cq is the quantum capacitance that informs on the density-of-states (DOS) as Cq ∝ e2DOS. This quantum rate concept is utilized to elucidate the ET rate constant k of electrochemical reaction as k = G/Cμ, where G is the quantum of conductance and Cμ is the electrochemical capacitance. This thesis presents a fundamental study, within the framework of the quantum rate theory, of the ET and transport processes in two kinds of molecular junctions (MJ): electroactive self-assembled monolayer (SAM) over electrodes and aromatic monolayers sandwiched between carbon electrodes. Time-dependent methods, such as impedance spectroscopy (IS) and electrochemical impedance-derived capacitive spectroscopy (ECS), were employed for this study. The impedance data were analyzed by equivalent circuit fitting, specifically as quantum resistive capacitive (RC) point contact. Redox SAMs were formed using Ferrocene-tagged peptides and thiol molecules. These redox SAMs feature Cq, which was determined by ECS, enabling the determination of k as = 2(G0/Cq), where G0 represents the universally known constant for quantum conductance, approximately 77.5 μS. The reciprocal of G0 defines the quantum resistance as Rq = 1/G0 ∼ 12,9 kΩ, establishing a quantum limit for ET. This demonstrates that the electrodynamics is governed by Rq and Cq elements. Furthermore, it was determined that Rq comprises two resistive components connected in series: the relaxation resistance (Rqt) and the combined resistance of solution and contact (Rs), leading to Rq ∼ 13 kΩ. Consequently, the interpretation of Rq within the quantum rate model prompted a reassessment of the meaning assigned to the charge transfer resistance Rct, revealing that Rq is equivalent to Rct. Moreover, it was demonstrated that regardless of the molecular backbone, the Cq states of the redox interface mediate the ET between electroactive free species and the electrode, conforming to maximum efficiency of electron transmittance. Specifically, it was proven that an increase in the number of quantum channels N, and consequently of Cq by almost 40%, was achieved through suitable energy level alignment between the level states of the free redox species with that of the DOS of the redox SAM. This exceptional setting allowed for the amplification of the Cq signal for the detection of a biological target. As a proof-of-concept, this amplification mechanism was applied for sensing the nonstructural protein 1 (NS1) biomarker of the dengue virus, resulting in an observed increase in sensitivity of redox capacitive biosensors by at least 1,000. However, it was evidenced that the acidity of the quantum capacitive interface affects the electron transfer mediation as a result of the electrostatic repulsion between the negatively charged surface and redox charged species. Furthermore, the determination of properties G and Cμ using SI measurement of the aromatic MJs demonstrated that G and k are correlated by Cμ, implying that the associated physical concepts studied separately by the electrochemist and physics are inherently related. The results obtained in this thesis demonstrate that the quantum rate model is a suitable theory enable to address phenomena involved with electron transmittance such as electron transfer, quantum conductance, and capacitance in different MJs.

A compreensão da transmissão de elétrons, incluindo a transferência eletrônica (TE) e o transporte, é essencial não apenas para a compreensão de sistemas biológicos, mas também para o desenvolvimento de componentes elétricos na busca pela fabricação de dispositivos eletrônicos. A teoria do quantum rate propõe uma velocidade quântica fundamental de primerios principios ν = e2/hCq, onde e é a carga elementar, h é a constante de Planck e Cq é a capacitância quântica, que informa sobre a densidade de estados (DOS em inglês) como Cq ∝ e2DOS. O conceito de ν é utilizado para elucidar a constante de velocidade de transferência de elétrons k de reações eletroquímicas, como k = G/Cμ, onde G é o quantum de condutância e Cμ é a capacitância eletroquímica. Esta tese apresenta um estudo fundamental, dentro do contexto da teoria do quantum rate, dos processos de TE e transporte de elétrons em dois tipos de junções moleculares (MJ em inglês): monocamadas electroativas auto-montadas (SAM em inglês) sobre eletrodos e monocamadas aromáticas ligadas entre eletrodos de carbono. Métodos dependentes do tempo como a espectroscopia de impedância (IS em inglês) e a espectroscopia capacitiva derivada de impedância (ECS em inglês), especificamente como um punto quântico resistivo capacitivo (RC). As SAMs redox foram formadas utilizando peptídeos e tióis marcados com ferroceno. Essas SAMs apresentam uma Cq, que foi obtida por ECS, permitindo a determinação de k como k = 2(G0/Cq ), onde a constante G0 ∼ 77,5 μS é a condutância quântica. O inverso de G0 define a resistência quântica como Rq = 1/G0 ∼ 12,9 kΩ, estabelecendo um limite quântico para a TE. Isso demonstra que a eletrodinâmica é governada por Rq e Cq. Além disso, foi determinado que Rq compreende dois componentes resistivos conectados em série: a resistência de relaxação (Rqt) e a resistência combinada da solução e do contato (Rs), resultando em Rq ∼ 13 kΩ. Consequentemente, a interpretação de Rq levou a uma reavaliação do significado atribuído à resistência de transferência de carga Rct, revelando que Rq é equivalente a Rct. Além disso, foi demonstrado que, independentemente do esqueleto molecular, os estados Cq da interface redox mediam a TE entre espécies eletroativas livres e o eletrodo, dentro de uma eficiência máxima de transmissão de elétrons. Especificamente, foi comprovado que um aumento no número de canais quânticos N, e consequentemente de Cq em cerca de 40%, foi alcançado por meio de um alinhamento adequado dos níveis de energia entre os estados dos espécies redox livres e a DOS do SAM. Essa configuração excepcional permitiu a amplificação do sinal Cq para a detecção de um alvo biológico. Como prova de conceito, esse mecanismo de amplificação foi aplicado para a detecção do biomarcador da proteína não estrutural 1 (NS1 em inglês) do vírus da dengue, resultando em um aumento observado na sensibilidade dos biossensores capacitivos redox em pelo menos 1.000 vezes. No entanto, foi evidenciado que a acidez da interface capacitiva quântica afeta a mediação da transferência de elétrons como resultado da repulsão eletrostática entre a superfície carregada negativamente e as espécies redox carregadas. Além disso, a determinação das propriedades G e Cμ por meio de medições SI das MJ aromáticas demonstrou que G e k estão correlacionados por meio de Cμ, o que implica que os conceitos físicos associados estudados separadamente pelos eletroquímico e pelos físicos estão intrinsecamente relacionados. Os resultados obtidos nesta tese demostram que o modelo do quantum rate é uma teoria adequada que permite abordar fenômenos envolvidos com a transmissão de elétrons como a transferência eletrônica, condutância quântica e capacitância em diferentes MJs.
Eletrônica molecular e eletroquímica: o caso de interfaces marcadas com ferroceno e de junções moleculares orgânicas estudadas por métodos dependentes do tempo
Keywords: Charge transfer; Impedance spectroscopy; Nanoeletronics; Tunneling; Quantum electrodynamics; Espectroscopia de impedância; Nanoeletrônica; Tunelamento; Eletrodinâmica quântica